2018
DOI: 10.4314/ijmu.v13i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cleft lip and palate in Brazilian children 2011 - 2015

Abstract: Cleft lip and cleft palate are birth defects of complex etiology. The aim of this study was to evaluate the occurrence of cleft lip and palate in Brazilian children. An ecological and descriptive study, based on data from the Live Birth Information System (SINASC / DATASUS) between years 2011 and 2015 in the cities of João Pessoa, Campina Grande, Patos, Cajazeiras, and Sousa (State of Paraíba) was developed. Information on the presence of congenital anomalies and cleft lip and palate, gender of neonate, birth-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…In this study, a higher frequency of cases of children with orofacial clefts born with normal weight was identified. This result is consistent with findings of Brazilian (23,24) and Thailand (28) studies which demonstrated that the majority of infants with orofacial clefts had normal birth weight.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, a higher frequency of cases of children with orofacial clefts born with normal weight was identified. This result is consistent with findings of Brazilian (23,24) and Thailand (28) studies which demonstrated that the majority of infants with orofacial clefts had normal birth weight.…”
Section: Discussionsupporting
confidence: 92%
“…Cleft palate alone is more common in women, while cleft palate and lip is more frequent among males, across various ethnic groups (20). In the present study, most children with clefts were males, corroborating similar results found in literature (2,(20)(21)(22)(23). Molecular and genetic studies are needed to better understand the differences between the types of oral clefts and gender (20).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 19 , 20 For maternal age, there is no consensus in the literature. Although the age group from 20 to 29 years was more predominant in this and other studies, 14 , 15 , 23 the literature also points to a higher occurrence of OC in children whose mothers were of intermediate age, up to 34 years of age, 16 , 22 , 23 and advanced age, from 35 years onwards. 25 Maternal age differences may have occurred due to possible methodological differences in the studies or possible confounding factors in the analyzed populations.…”
Section: Discussionsupporting
confidence: 53%
“…25 Also, the prevalence of the disease in Brazil was about 5.2/10 000. 26 Compared with some cities in our country, we found that the prevalence of cleft lip and/ or palate in Guangdong province was lower than that in Beijing (18.9/10 000) 9 and Gansu province (13.48/10 000). 27 The results of our present study revealed the epidemiological characteristics and spatio-temporal trends of cleft lip and/or palate in Guangdong, the most economically developed province in South China.…”
Section: Discussionmentioning
confidence: 48%